Legal approach to prevention crime in Islamic finance in Malaysia and Iran / Ezani Yaakub ... [et al.] - Yaakub, Ezani; Husin, Asmak; Shaharuddin, Solahuddin; Mahdavi, Aref (2011)
This paper focuses on crime prevention in Islamic Financial Institution in Malaysia. Current practice indicates that due to historical background which separate Islamic and Civil law, crime prevention within Islamic financial criminology framework is obscured. Conflicts of power exist among authoritative bodies; Civil and Syariah Court, Syariah Advisory Boards, National and State Fatwa Councils shows insufficient legal system to support the growth Islamic Financial Institutions in Malaysia. As a result, Islamic financial crime prevention is done within the scope of conventional framework. This paper aims to (i) to explain the concept of criminology from Islam’s view; ii)to examine the background of Islamic financial criminology crime prevention in banking system in Malaysia and comparing this practices to country, Iran;(iii) to make recommendation on legal improvement to support Islamic financial system in Malaysia.